2023
DOI: 10.26803/ijlter.22.9.15
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Interactive Reading Models in Improving Early Students Language Skills

Gyan Puspa Lestari,
Syihabuddin Syihabuddin,
Aceng Kosasih
et al.

Abstract: This study aims to examine the effectiveness of interactive reading models in improving early childhood receptive and productive language skills. The interactive reading model used in this study consists of the traditional, the attention-focused, and the mind-map interactive reading models. This study used an experimental research method with a pre-posttest design. The sample in this study was 500 participants, with a composition of 150 people each in the traditional, focused attention, mind-map methods, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…Research done by Majumdar et al (2021) also found out the description of the students' online reading profiles can be monitored through the use of reading logs integrated with a learning application. Strategies have been used to foster reading motivation, such as inspirational stories, digital reading text, and expository text (Al Sultan, 2023;Laeli et al, 2022;Lestari et al, 2023;Quinonez-Beltran et al, 2023). Encouraging students to nurture their reading logs will make them enjoy reading and develop their capacity for reading.…”
Section: Introductionmentioning
confidence: 99%
“…Research done by Majumdar et al (2021) also found out the description of the students' online reading profiles can be monitored through the use of reading logs integrated with a learning application. Strategies have been used to foster reading motivation, such as inspirational stories, digital reading text, and expository text (Al Sultan, 2023;Laeli et al, 2022;Lestari et al, 2023;Quinonez-Beltran et al, 2023). Encouraging students to nurture their reading logs will make them enjoy reading and develop their capacity for reading.…”
Section: Introductionmentioning
confidence: 99%